2021
DOI: 10.7759/cureus.15082
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Sepsis Pathogens and Resistance Patterns in a South Asian Tertiary Care Hospital

Abstract: The aim of this study was to determine common microorganisms causing septicemia and their antimicrobial sensitivities in patients admitted to a tertiary care hospital. MethodsA cross-sectional study was conducted using clinical criteria to diagnose patients as having septicemia where blood for culture and sensitivity (CS) was sent to the laboratory of a tertiary care hospital, Rehman Medical Institute, (Peshawar), Pakistan, during 2019. All patients diagnosed with septicemia regardless of age and gender were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A study conducted in Nepal reported that Gram-negative organisms were non-resistant to chloramphenicol and tigecycline showed [16]. An Indian study demonstrated that the majority of 33 Klebsiella pneumoniae and E. coli isolates were non-resistant to meropenem, amikacin, chloramphenicol and ciprofloxacin [7]. Chloramphenicol is a safe alternative.…”
Section: Chloramphenicol Advantage Over Colistin Resistance In Sepsis...mentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted in Nepal reported that Gram-negative organisms were non-resistant to chloramphenicol and tigecycline showed [16]. An Indian study demonstrated that the majority of 33 Klebsiella pneumoniae and E. coli isolates were non-resistant to meropenem, amikacin, chloramphenicol and ciprofloxacin [7]. Chloramphenicol is a safe alternative.…”
Section: Chloramphenicol Advantage Over Colistin Resistance In Sepsis...mentioning
confidence: 99%
“…Another study reported that colistin-resistant Klebsiella isolate had mutations in the mgrB, PhoP and PhoQ genes [45]. Pakistani and East Indian studies have reported colistin resistance due to the high use of meropenem and colistin in patients with sepsis [7,41]. Another study demonstrated that the prevalence of colistin resistance among Escherichia coli and Klebsiella pneumoniae isolates was very high [46].…”
Section: Chloramphenicol Advantage Over Colistin Resistance In Sepsis...mentioning
confidence: 99%
See 2 more Smart Citations
“…2 Clinicians have developed various screening and prediction tools to screen high-risk cases or patients with presumably poor outcomes incorporating various clinical and laboratory parameters. 3,4 qSOFA score, SOFA score, and SIRS have been used in routine by treating teams to categorize the patients according to disease severity. 5,6 Some work has been published in recent years regarding the role of various scores in predicting mortality in patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%